Continuous Professional Development in Mathematics: Higher Order Thinking Skills - Chaurasia , P. K. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Teaching high order thinking skills (HOTS) is currently at the centre of educational attention. In general, measures of high order thinking include all intellectual tasks that call for more than the retrieval of information. Five fundamental HOTS have been identified in Mathematics. They are: problem solving skills, inquiring skills, reasoning skills, communicating skills and conceptualizing skills. These fundamental and intertwining ways of learning mathematics, thinking and using mathematical knowledge are considered important in mathematics education. In fact, many of students‟ problems in learning mathematics originate from their weaknesses in one or more of these skills. Students are expected to enhance the development of these skills and use them to construct their mathematical knowledge, and hence engage in life-long learning.